Strengthening the Core Business of Farmers Markets through Strategic Business Planning - Connell, David J.; Hergesheimer, Christopher (Journal of Agriculture, Food Systems, and Community Development, 2014)
The current period of growth in the number of farmers markets is associated with higher demand for local food but also leads to more competition among farmers markets. Dealing with increased competition challenges the way that farmers markets are used to operating. In this commentary, the authors discuss how a business-oriented approach to strategic planning may help farmers markets respond to industry-wide changes. We first focus on what we refer to as the core business of a farmers market, whereby a farmers market can view itself as a business entity that functions separately from its vendors. We extend this discussion to strategic business planning and how competitive analysis can be used to better understand and thereby strengthen a farmers market's position in an increasingly competitive marketplace. Ideally, a business-oriented perspective should not compromise the special qualities of a farmers market but serve to enhance these qualities and add to the growth and development of a farmers market. The insights in this commentary are drawn from the general experiences of the authors.